Mobile application for the visually impaired - Tan, Darren Yung Shen (2020)
This is a mobile application project designed to assist visually impaired users. The core function of the application is to help users interpret the things in their surrounding without the need to get in much contact with it in order to know what it is. This function is more commonly known as object detection. Other than that, there would be additional features which can contribute in the visually impaired users' daily life. They will be able to experience a possible self-relying usability of a mobile application. Developing this mobile application involves the usage of Java and Android Studio as its integrated development environment. The interface and some additional features would utilize much of Java programming. An android device will be used for testing the application constantly. This project will be running on prototyping methodology, hence there will be lots of testing conducted on the application. The goal is to ensure our visually impaired users can experience an unsophisticated navigation within the application and frequent testing by prototyping can help in achieving the goal.